Parentalidad y la salud afectiva en los estudiantes de la Escuela de Educación Básica John F. Kennedy, año 2019 - Calero Ruiz, Dennisse Ariana (2019)
The family environment is composed in the space that lives a group of relatives who assist in economic life in the upbringing and education of children. Despite the importance of the family environment in learning, it has been observed that students live in a negative context that focuses on the educational environment, children and adolescents with attitudes and behavior that affect the interaction of parents and children; student-teachers and between classmates. Attitude and behavior that help to equate as people of human quality so that they can function in society. Through the collection of information made to parents, teachers and students, the insufficiency of family education could be identified and teachers spend little time referring to the harmfulness of the negative environment and its influence on the emotional and affective state. Parenthood is still a determining factor, since parents are the first educators of their children; of them receive the first teaching, because that education demands patience, tolerance, altruism and sacrifice, being more natural to find these qualities in the parents ". The family offers favorable conditions and if it does not comply, leave it to the care of any human being that constitutes a risk to society. he proposal consists of developing innovative strategies with activities that contribute to a positive and harmonious environment with your family and in the classroom, improving interaction with society and adequately develop your emotions, so the student is active, happy and motivated so that achieve a formative learning.